Vesta: A Secure and Autonomic System for Pervasive Healthcare - Zhu,Y; Sloman,M; Lupu,EC; Keoh,SL (ICST, 2009)
The proliferation of low-power wireless communications and handheld devices has facilitated the development of pervasive systems for healthcare applications. This paper describes a body sensor network comprising a personal controller, various biosensors and actuators for pervasive healthcare. Various physiological parameters such as heart rate or blood oxygen level can be continuously monitored. The growing complexity of such systems, however, poses challenges for system management and security. In this paper we present a secure autonomic body sensor network called Vesta which makes use of the extensible architecture pattern of a self managed cell (SMC). A policy-driven management paradigm supports adaptability to contextual changes by applying event-condition-action rules. Fine-grained access control of the system is realized through authorization policies. Experimental evaluation shows that it is viable and practical for real-world pervasive healthcare.